Modeling the role of nursing in school health control: Implementation through audiovisual instruments - Concha Gacitúa, Paula (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The pandemic forced the suspension of practical activities of the nursing career, adapting them to the online modality, making it difficult to develop the procedural skills of the students. As an alternative, 6 demonstrative audiovisual capsules of a control were built, with the subsequent explanation of these. It stands out that 90% of the students developed the skills, 84% passed the unit test and 87% strongly agree that the strategy facilitated their learning. It is concluded that the modeling strategy with audiovisual media is an effective methodology for the development of these skills.